Implementasi Manajemen Strategi Rumah Zakat Indonesia dalam Pembinaan Mualaf di Kabupaten Kuningan - Putri, Silva Nabila; Rustandi, Ridwan (Tadbir: Jurnal Manajemen Dakwah, 2025)
This study aims to examine the implementation of environmental scanning, strategy formulation, strategy implementation, and evaluation and control in the muallaf (convert) empowerment program at Rumah Zakat Indonesia. This research employs a qualitative approach with a case study method and a constructivist paradigm. The theory used is strategic management by Wheelen and Hunger (2006), which includes environmental scanning, strategy formulation, strategy implementation, and evaluation and control. The findings show that environmental scanning is conducted through SWOT analysis and a needs assessment of muallaf; strategy formulation is developed based on the organization’s vision, mission, and cross-institutional collaboration; strategy implementation is carried out through empowerment programs based on Islamic, social, and economic aspects, facilitated by volunteers; while evaluation and control are conducted through regular monitoring and reporting, although the evaluation system has not yet been fully optimized. This study highlights the importance of an adaptive and collaborative strategic management approach in enhancing the effectiveness of muallaf empowerment in a sustainable manner.